IMPLEMENTING INFORMATION TECHNOLOGY: AN ALTERNATIVE FOR URBAN RESETTLEMENT PROGRAM - Bauni Hamid (DIMENSI (Journal of Architecture and Built Environment), 2001)
Revitalizing slum-area has been recognized as one of the most complicated parts in urban resettlement program. With such a context we need a particular mode of communication to initiate and generate the project based on people's own aspiration. There are problem characteristics here, which are usually executed by Information Technology (IT). It is a potential to overcome the problem by using IT based on its ability to manage abundant information with various variables. At least there are three prospective opportunities in applying IT in this area. Firstly, it is the role of visualization, where computer can execute several visual features of the projects, which will be more representative than the previous ones. Secondly, it is the role of IT in generating the customization process to everyone involved in the projects. The last is the role of IT as executing tool for project's database management.